Extent of Mesoappendix of Vermiform Appendix in Bangladeshi People - Rahman, Md Mahbubur; Khalil, Mohsin; Khalil, Mansur; Sultana, Seheli Zannat; Mannan, Sabina; Nessa, Akhtarun; Ahamed, M Shibbir; Parvin, Bilkis; Islam, Md Tarequl; Siddiquee, Fayela Saorun (Journal of Bangladesh Society of Physiologist, 2009)
Background: The mesentery of the appendix extends almost to the appendicular tip along the whole tube or may not be to the tip. The mesoappendix has a free border which carries the blood supply to the organ. Failure of the mesoappendix to reach the tip probably reduces the vascularization of the tip of the organ making it more liable to become gangrenous and hence early perforation occurs during inflammation. Objective: This cross sectional study was carried out to advance our knowledge regarding the extent of mesoappendix in Bangladeshi people and also to find out the variations in the anatomical positions of the vermiform appendix in Bangladeshi population and their distribution according to the sex. Methods: A total of 100 (60 male and 40 female) specimens of vermiform appendix were collected of different age and sex during postmortem examination in the morgue of Mymensingh Medical College from July 2006 to June 2007. Data was collected by convenient sampling technique. Results: In this study pelvic position of the vermiform appendix were common in both sexes. The two thirds extension of mesoappendix was found in 45% cases where as in pelvic position it was 26 (14 male and 12 female) cases. Half and whole extension of mesoappendix were found in 31% and 24% cases respectively. Among half extension of mesoappendix, retrocaecal position were found to be more (12) than other positions. In whole extension of vermiform appendix pelvic position were found to be common (16) than others. Conclusion: This study provides certain basic information of extent of mesoappendix of vermiform appendix of Bangladeshi population which is responsible for vascularization of the organ and severity during inflammation. Key words: Vermiform appendix, Mesoappendix DOI: 10.3329/jbsp.v4i1.4065 J Bangladesh Soc Physiol. 2009 June; 4(1): 20-23